Analisis Kebijakan Tata Niaga Subsidi LPG 3 Kg di Tingkat Daerah: Studi Implementasi di Kabupaten Bantul - Elmi Wahyuni; Budiman Rusli; Candradewini Candradewini (Jurnal Ilmiah Global Education, 2026)
The LPG 3 Kg subsidy policy is an important instrument of social protection; however, its implementation continues to face various distribution and governance challenges at the local level. This study aims to analyze the implementation of the LPG 3 Kg subsidy distribution policy in Bantul Regency, identify key implementation problems, and formulate the most feasible policy alternatives based on the rational policy analysis framework of Patton and Sawicki. The study employs a mixed-methods approach with a convergent design, combining qualitative data (in-depth interviews with local government officials, Pertamina, Hiswana Migas, agents, and LPG outlets) and quantitative data (a survey of 105 LPG 3 Kg subsidy users), which are analyzed using descriptive statistics and multiple linear regression. The findings indicate that policy implementation is characterized by persistent targeting inaccuracies, dominance of purchases through informal retailers, and weak administrative operability in the application of the Merchant Apps Pangkalan (MAP). Regression analysis reveals that the fairness variable (β = 0.479; p < 0.001) and administrative operability (β = 0.372; p < 0.001) are the most significant determinants of policy effectiveness. Based on the evaluation of policy alternatives using an evaluation matrix, strengthening the NIK-based verification system and integrating socio-economic data with MAP is identified as the most rational and feasible policy option for implementation in Bantul Regency. This study recommends improving data-driven LPG 3 Kg distribution governance as a strategic measure to enhance the effectiveness, equity, and accountability of energy subsidies at the local level.